Influence of basalt fiber on performance of thin overlayer asphalt mixtures based on multiple experimental methods - Li, Bo; Zhou, Yangyang; Wu, Zhengguang; Kang, Aihong; Wu, Bangwei; Luo, Chufan (Frontiers in Energy Research, 2023)
Because of the fast deterioration speed of the surface function of conventional asphalt pavement, thin overlayer with many advantages has been applied to the pavement surface. However, due to problems such as insufficient stripping resistance and cracking resistance, the performance of the thin overlayer needs to be further improved. To achieve this target, basalt fiber was introduced into two types of thin overlayer asphalt mixtures (Open graded friction course, OGFC-5, and Stone matrix asphalt mixture, SMA-5). The wheel tracking test and uniaxial penetration test for high temperature deformation resistance, low temperature bending beam test and indirect tensile asphalt (IDEAL) cracking test for cracking resistance, cantabro test for stripping resistance, and friction coefficient test for skid resistance were conducted to evaluate various performance of thin overlayer asphalt mixtures, along with the dynamic modulus test for dynamic mechanical response. The results showed that adding basalt fiber could enhance the high temperature deformation resistance, low temperature cracking resistance, intermediate temperature cracking resistance and stripping resistance of the thin overlayer, while having no significant impact on skid resistance. Furthermore, adding basalt fiber could increase the modulus in the high temperature region and decrease the modulus in the low temperature region of the thin overlayer asphalt mixtures, indicating thin overlayer with basalt fiber presenting superior both high temperature and low temperature performance. In addition, the evaluation indexes of SLT and SHT proposed from dynamic modulus test exhibited good consistency with the results of the performance tests.